Medical Cannabis and the Treatment of Obstructive Sleep Apnea: An American Academy of Sleep Medicine Position Statement - Ramar, Kannan (J Clin Sleep Med, 2018)
The diagnosis and effective treatment of obstructive sleep apnea (OSA) in adults is an urgent health priority. Positive airway pressure (PAP) therapy remains the most effective treatment for OSA, although other treatment options continue to be explored. Limited evidence citing small pilot or proof of concept studies suggest that the synthetic medical cannabis extract dronabinol may improve respiratory stability and provide benefit to treat OSA. However, side effects such as somnolence related to treatment were reported in most patients, and the long-term effects on other sleep quality measures, tolerability, and safety are still unknown. Dronabinol is not approved by the United States Food and Drug Administration (FDA) for treatment of OSA, and medical cannabis and synthetic extracts other than dronabinol have not been studied in patients with OSA. The composition of cannabinoids within medical cannabis varies significantly and is not regulated. Synthetic medical cannabis may have differential effects, with variable efficacy and side effects in the treatment of OSA. Therefore, it is the position of the American Academy of Sleep Medicine (AASM) that medical cannabis and/or its synthetic extracts should not be used for the treatment of OSA due to unreliable delivery methods and insufficient evidence of effectiveness, tolerability, and safety. OSA should be excluded from the list of chronic medical conditions for state medical cannabis programs, and patients with OSA should discuss their treatment options with a licensed medical provider at an accredited sleep facility. Further research is needed to understand the functionality of medical cannabis extracts before recommending them as a treatment for OSA. CITATION: Ramar K, Rosen IM, Kirsch DB, Chervin RD, Carden KA, Aurora RN, Kristo DA, Malhotra RK, Martin JL, Olson EJ, Rosen CL, Rowley JA; American Academy of Sleep Medicine Board of Directors. Medical cannabis and the treatment of obstructive sleep apnea: an American Academy of Sleep Medicine position statement. J Clin Sleep Med. 2018;14(4):679–681.